KORELASI KADAR MATRIX METALLOPROTEINASES 3 (MMP-3) DENGAN DERAJAT BERATNYA OSTEOARTRITIS LUTUT - Eka Imbawan, IGN; Raka Putra, Tjokorda; Kambayana, Gede (journal of internal medicine, 2011)
Osteoarthritis (OA) is one type of arthritis which commonly found especially in elderly and become the common cause ofdisability in elderly people. Recently known that immunologic respons and homeostasis of cartilage metabolism have animportant role, and MMP-3 as one of degradative enzyme which has a pivotal role in OA patogenesis. Aim of this studyis to determine correlation between level of MMP-3 and radiographic grading of knee OA, in Sanglah Hospital, DenpasarBali. An analytical cross sectional study was carried out in Policlinic Sanglah Hospital, enrolled 76 samples with kneeOA. Of all sample, 32 (42.1%) were males and 44 (57.9%) famales. The mean of MMP-3 serum level is 25.2 ± 20.7ng/ml. Radiographic grading of knee OA based on Kelgren and Lawrence criteria 4 (5.3%) grade 1,29 (38.3%) grade 2,28 (36.8%) grade 3 and 15 (19.7%) grade 4. The mean level of MMP-3 on grade 1 group is (24.7 ng/ml), grade 2 (17.8ng/ml), grade 3 (28.3 ng/ml) and grade 4 is 32.8 ng/ml. Using Spearman!s analyses, there were signiÞ cant correlationbetween MMP-3 and radiographic grading of knee OA (r = 0.25 and p = 0.03).There were signiÞ cant positive correlation between MMP-3 and radiographic grading of knee OA.